Blood stem cell products: Toward sustainable benchmarks for clinical translation. (15th January 2013) - Csaszar, Elizabeth; Cohen, Sandra; Zandstra, Peter W.
Abstract Robust ex vivo expansion of umbilical cord blood (UCB) derived hematopoietic stem and progenitor cells (HSPCs) should enable the widespread use of UCB as a source of cells to treat hematologic and immune diseases. Novel approaches for HSPC expansion have recently been developed, setting the stage for the production of blood stem cell derived products that fulfill our current best known criteria of clinical relevance. Translating these technologies into clinical use requires bioengineering strategies to overcome challenges of scale‐up, reproducibility, and product quality assurance. Clinical‐scale implementation should also define criteria and targets for cost‐effective cell manufacturing. As production strategies become more effective, new opportunities in the therapeutic use of ex vivo expanded hematopoietic cell products will emerge. Herein we examine key technological milestones that need to be met in order to move ex vivo expanded HSPC therapies from the bench‐top to the bedside in a robust and reliable manner.